2019
DOI: 10.1073/pnas.1814850116
|View full text |Cite
|
Sign up to set email alerts
|

OR14I1 is a receptor for the human cytomegalovirus pentameric complex and defines viral epithelial cell tropism

Abstract: A human cytomegalovirus (HCMV) pentameric glycoprotein complex (PC), gH–gL–UL128–UL130–UL131A, is necessary for viral infection of clinically relevant cell types, including epithelial cells, which are important for interhost transmission and disease. We performed genome-wide CRISPR/Cas9 screens of different cell types in parallel to identify host genes specifically required for HCMV infection of epithelial cells. This effort identified a multipass membrane protein, OR14I1, as a receptor for HCMV infection. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(53 citation statements)
references
References 72 publications
0
53
0
Order By: Relevance
“…Two glycoprotein complexes on the HCMV surface drive broad host cell tropism [22]. A pentameric complex of glycoprotein H (gH; UL75), gL (UL115), UL128, UL130 and UL131A mediates entry into epithelial and endothelial cells [23][24][25][26][27][28], possibly through engagement of neuropilin-2 [29] or the olfactory receptor OR14I1 [30] on the host cell. A trimeric complex of gH, gL and gO (UL74) is sufficient for entry into fibroblasts and is also necessary for entry into pentamer-requiring cell types by promoting membrane fusion [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Two glycoprotein complexes on the HCMV surface drive broad host cell tropism [22]. A pentameric complex of glycoprotein H (gH; UL75), gL (UL115), UL128, UL130 and UL131A mediates entry into epithelial and endothelial cells [23][24][25][26][27][28], possibly through engagement of neuropilin-2 [29] or the olfactory receptor OR14I1 [30] on the host cell. A trimeric complex of gH, gL and gO (UL74) is sufficient for entry into fibroblasts and is also necessary for entry into pentamer-requiring cell types by promoting membrane fusion [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…HCMV entry into host cells is extremely dynamic due to the usage of a variety of cellular entry receptors during virus-cell interactions [21][22][23][24]. It has been shown that depending on the cell type, HCMV can utilize multiple target cell receptors, including cell surface heparan sulfate (HS), different cellular integrins, platelet-derived growth factor receptor alpha (PDGF-Rα), neuropilin-2 and epidermal growth factor receptor (EGF-R), for cellular entry [25][26][27][28][29][30][31]. On the flip side, HCMV's multiple viral glycoproteins, including gB, gO, and gH-gL, engage these structurally and functionally unrelated receptors to penetrate cellular defenses.…”
Section: Introductionmentioning
confidence: 99%
“…It is now accepted that the two main host cell receptors for HCMV involve the platelet-derived growth factor receptor α (PDGFRα) [66][67][68] and Neuropilin 2 (Nrp2) [55]. In addition, other cellular host factors were described as facilitators of viral entry such as the olfactory receptor family member OR14I1 [69], the adipocyte plasma membrane-associated protein (APMAP) [70], CD46 [71], and CD147 [72]. However, the biological relevance of this multitude of receptors remains to be understood.…”
Section: Hcmv Antigens As Vaccine Candidatesmentioning
confidence: 99%